Copper(II) Triflate Catalyzed Rearrangement of Amino 2,3-Epoxides to α-Amino Ketones - Chitsomkhuan, Saranya; Buakaew, Supawadee; Samec, Joseph S. M.; Chuawong, Pitak; Saymaya, Jenjira; Kuntiyong, Punlop; Pluempanupat, Wanchai; Akkarasamiyo, Sunisa (Synlett, 2024)
α-Amino ketones were synthesized by a Meinwald rearrangement of biomass-based amino epoxides using copper(II) triflate as a catalyst. The regioselectivity of the rearrangement can be rationalized in terms of the reaction proceeding via the most stable carbocationic intermediate to give various α-amino α′-aryl ketones in moderate to good yields. This is an attractive method to prepare α-amino ketones using a benign and inexpensive catalyst.
Keywords: Meinwald rearrangement; amino ketones; amino epoxide; copper catalysis; copper triflate